An Exploratory Study of Individual and Parental Techniques for Limiting Loot Box Consumption. - Gong, Liurun; Rodda, Simone N. (International Journal of Mental Health & Addiction, 2022)
Loot boxes can provide a competitive advantage to gamers, but there is limited information on how to self-regulate purchases. This study aimed to identify the behaviour change techniques (BCTs) for the self-regulation of loot boxes. A thematic analysis was applied to 777 statements obtained from a systematic search of websites containing real-world experiences. Eleven BCTs and 47 strategies were identified for self-regulation including antecedents (avoidance, environmental restructuring), substitution (spending game credits not money), identity (purchasing loot boxes is a waste of money and inconsistent with values), self-control (use of willpower), and a comparison of risk versus out-right purchases. A further eight BCTs and 38 strategies were identified that could be administered by parents including environmental restructuring (removing stored credit cards, limiting access to games), persuasion (better ways to spend money, budgeting), and monitoring (observing play or expenditure). Multi-faceted support for self-regulation may be needed for children and adult consumers of loot boxes.